Analisis SWOT Dalam Menentukan Strategi Keberlanjutan Usaha Toreko - Varah Iftitah Aulia; Juliana Kadang; Harnida Wahyuni Adda (Pusat Riset dan Inovasi Nasional, 2023)
Business continuity, which is closely related to the long-term maintenance of the system in accordance with environmental, economic and social considerations, is an important point that needs to be considered by every MSME actor. The store business is one of the new MSMEs that is of concern so that it continues to carry out business continuity by being carried out based on currently related internal and external factors. Toreko created a unique business idea from brownies, innovating brownies into brownies cookies and using raw materials from mocaf flour. mocaf itself is a modified cassava flour product. The purpose of this article is to describe and analyze the sustainability position of the toreko business through a SWOT analysis, formulate alternative strategies that can be implemented by the toreko after knowing the position of the sustainability position of the business it has. The aggressive strategy is the main choice strategy obtained from the results of IFAS and EFAS. The SWOT matrix is used to determine and arrange the steps for implementing the strategy related to the choice of strategy. An aggressive strategy is carried out until the threat that the store has is smaller than the opportunities that exist. Improving sales promotions and maintaining satisfaction with customer loyalty is the key to realizing business continuity properly.